Is 24/7 remote patient management in heart failure necessary? Results of the telemedical emergency service used in the TIM‐HF and in the TIM‐HF2 trials. (28th June 2021) - Winkler, Sebastian; Koehler, Kerstin; Prescher, Sandra; Koehler, Magdalena; Kirwan, Bridget‐Anne; Tajsic, Milos; Koehler, Friedrich
Abstract: Aims: Telemedical emergency services for heart failure (HF) patients are usually provided during business hours. However, many emergencies occur outside of business hours. This study evaluates if a 24/7 telemedical emergency service is needed for the remote management of high‐risk HF patients. Methods and results: The study included 1119 patients merged from the TIM‐HF and TIM‐HF2 trials [age 69 ± 11, 73% male, left ventricular ejection fraction 37% ± 13, 557 New York Heart Association (NYHA) II/562 NYHA III]. Patients received a 24/7 physician‐guided emergency service provided by the telemedical centre (TMC) in addition to remote management within business hours. During emergency calls, patient status, symptoms, electronic patient record, and instant telemonitoring data were evaluated by the TMC physician. Following diagnosis, patients were referred for hospital admission or instructed to stay at home. Apart from the TMC, patients could place a call to the public emergency service at any time. Seven hundred sixty‐eight emergency calls were placed over 1383 patient years (0.56 calls/patient year). Five hundred twenty‐six calls (69%) occurred outside business hours. There were 146 (19%) emergency calls for worsening HF, 297 (39%) other cardiovascular, and 325 (42%) non‐cardiac causes, with a similar pattern inside and outside business hours. Of the 1119 patients, 417 (37%) placed at least one emergency call. Patients with NYHA Class III, higher N‐terminal prohormone of brain natriuretic peptide (>1.400 pg/mL) levels, ischaemic aetiology of HF, implanted defibrillator, and impaired renal function had a higher probability of placing emergency calls. During study follow‐up, patients who made an emergency call had a higher all‐cause mortality (22% vs. 11%, P = 0.007 in TIM‐HF; 16% vs. 4%, P < 0.001 in TIM‐HF2) and more unplanned hospitalizations (324 vs. 162, P < 0.001 in TIM‐HF; 545 vs. 180, P < 0.001 in TIM‐HF2). Of the total 1, 211 unplanned hospital admissions, 492 (41%) were initiated by a patient emergency call. Three hundred seventy‐nine calls (49%) were placed to the TMC, whereas 389 calls (51%) were made to the public emergency service. Three hundred twenty‐six (84%) of the calls to the public emergency service resulted in acute hospitalizations. The TMC initiated 202 (53%) hospital admissions; 177 (47%) patients were advised to stay at home. All patients that remained at home were alive during a prespecified safety period of 7 days post‐call. Diagnoses made by the TMC physician were confirmed in 83% of cases by the hospital. Conclusion: A telemedical emergency service for high‐risk HF patients is safe and should operate 24/7 to reduce unplanned hospitalizations. Emergency calls could be considered as a marker for higher morbidity and mortality.